Delivering sustainable growth in Africa African farmers and firms in a changing world - Takahiro Fukunishi (Editor) (Basingstoke Palgrave Macmillan, 2014)
The economic situation in Sub-Saharan Africa has recently undergone a process of change. After a long period of stagnation during the 1980s and 1990s, GDP per capita has shown significant growth in the 2000s. Although the growth rate is lower than that of East Asia, it is significantly higher than that in previous decades. The most significant factor yielding the better economic performance is the increase in commodity prices including oil, mineral and agricultural products, which are the main export products for most African countries. Another factor has been the scaling up of aid flows following the commencement of the Millennium Development Goals. The enhanced commitment of the donor community increased aid flow to Africa, which in turn increased GDP through consumption of locally sourced products and services, such as with the construction industry.
Includes bibliographical references and index.
Keywords: Agriculture --Economic aspects --Africa, Sub-Saharan.